Determinant factors of immediate outcomes of Neonatal Respiratory Distress Syndrome in Gondar, Ethiopia - Yousif Abdalla Alzubair; Yohannes Hailu; Koku Sisay Tamirat (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2022)
Introduction: Respiratory Distress Syndrome (RDS) is a frequent neonatal emergency worldwide. The prevalence varies with gestational age (GA) being higher among preterm babies. Preterm birth is the world's primary cause of newborn deaths and RDS is the leading cause of death in premature infants, including in Ethiopia. Objectives: To identify the determinant factors of the immediate outcomes of RDS in the neonatal intensive care unit (NICU), University of Gondar Specialized and Comprehensive Hospital (UoGSCH). Method: A hospital-based prospective descriptive analytical cross-sectional study was conducted from February to September 2020. Results: A total of 162 neonates were enrolled; there were 87 (53.7%) males and 75 (46.3%) females. Of these 106 (65.4%) were discharged with improvement, 4 (2.5%) discharged with complications, and 52 (32.0%) died; 50% of deaths occurred within the first 24 hours of age. The odds of mortality for those admitted below 6 hours of age was 6.14 times higher (AOR=6.14, 95% CI:1.63 23.03) than those admitted aged 6 hours and above. Babies born to primiparous mothers were more than twice as likely to die (AOR=2.49, 95% CI:1.05 5.87) than babies born to multiparous mothers. Neonates who were delivered in other facilities had 3.78 times increased odds of mortality (AOR=3.78, 95% CI: 1.23 11.57). Conclusion: Age at admission, site of referral, parity and gestational age (GA) had a significant association with neonatal mortality due to RDS.